- - Villarroel, Raúl (Acta Bioethica, 2000)
Trying to overcome difficulties posed by philosophical reflection to the revitalization of a project for achieving convergence among the diversity of moral criteria - typical of our epoch- a peculiar understanding of Bioethics, based on hermeneutical clues, is proposed. By so doing, we pretend to surpass in a legitimate way the totality of difficulties caused by the tension and discontinuity between cognitive and moral developments in two significant areas: health and environment. For achieving this aim we propose to pass along from the complete and definitive system of scientificistic reduccionism to the differencial interpretative border, where both dimensions are visualized rather from an intrinsically problematic condition, conjectural and unforeseeable, permanently reticent to whatever interpretative restriction.